Avaliação dos impactos dos índices de controle urbanístico: um estudo de cenários urbanos do bairro Vila Cabral, Campina Grande, PB, Brasil - Silva, Jaqueline Brandão da (2021)
The current urban growth model in Brazil can be associated with several problems of spatial performance. The action of different urbanizing agents influences the shape and dynamics of cities, enhancing urban dispersion and low built density. Thus, this research assesses the impacts of the current model of urban legislation on the production of space. From a methodological point of view, this is a quantitative and qualitative analysis of a homogeneous sample of the urban fabric of the Vila Cabral neighborhood, located in the city of Campina Grande, Paraíba. Two analytical scenarios were constructed relating to the years 2005 and 2020. The impacts of urban control indexes (provided for in the Land Use and Occupation Legislation), used organically by different planning agents in this period, were analyzed. The following procedures were applied: (i) literature review; (ii) shape analysis – Systemic decomposition; (iii) configurational analysis – Angular segment analysis and (vi) objective analysis – Parametric analysis of the diversity of uses; and parametric analysis of urban density (population and built). Then, these analyzes were also processed for three predictive scenarios, built to assess the impacts of urban control indices in their maximum legislated potential. The results obtained showed that both in organic growth scenarios (2005 and 2020) and in predictive scenarios, the neighborhood shows little land use, below the ideal recommended by the literature. It is also noteworthy that the association of different methodological procedures strengthens the urban analysis process. Predictive scenarios can foresee the spatial impacts on the quality of the built space, helping in decision-making in the urban planning process.